Tin and Nickel Influence on the Structure and Properties of the Leaded Bronze Obtained by Means of the Centrifugal Casting - Klochkov N. S. Nikolai Sergeevich; Egorov Yu. P. Yuri Petrovich; Mapelli K. Karlo; Zabrodina I. K. Irina Konstantinovna (Functional and Special Structural Materials, Technologies of Coatings, Strengthening and Hardening, 2016)
Title screen